2006
DOI: 10.1194/jlr.m600077-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of de novo phosphatidylinositol synthesis

Abstract: Mechanisms that function to regulate the rate of de novo phosphatidylinositol (PtdIns) synthesis in mammalian cells have not been elucidated. In this study, we characterize the effect of phorbol ester treatment on de novo PtdIns synthesis in C3A human hepatoma cells. Incubation of cells with 12-O-tetradecanoyl phorbol 13-acetate (TPA) initially (1-6 h) results in a decrease in precursor incorporation into PtdIns; however, at later times (18-24 h), a marked increase is observed. TPA-induced glucose uptake from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The rate of PC biosynthesis does not appear to be influenced significantly by the rate of Cho transport in most nonproliferating cells such as rat liver and rat kidney cortex 5455. In addition, for these nonproliferating cells, Cho is metabolized through both the CDP-Cho pathway and the betaine oxidation pathway.…”
Section: Discussionmentioning
confidence: 96%
“…The rate of PC biosynthesis does not appear to be influenced significantly by the rate of Cho transport in most nonproliferating cells such as rat liver and rat kidney cortex 5455. In addition, for these nonproliferating cells, Cho is metabolized through both the CDP-Cho pathway and the betaine oxidation pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Triacsin C is a fatty acid analogue that has been shown to inhibit ACSL 1, ACSL3 and ACSL4. This compound causes apoptosis of many cancer cell types, including breast [71, 110113], and has been demonstrated to inhibit the growth of xenograft tumors [110]. Lipid droplets comprise an emerging target in a number of diseases, including cancer, and it has been suggested that the lipid droplet protein, PLIN2, might make an effective target [114].…”
Section: Discussionmentioning
confidence: 99%
“…This synthase produces L-myo-inositol 1-phosphate by the transformation of D-glucose-6-phosphate (Lohia et al, 1999). During de novo PI synthesis in eukaryotes, myoinositol-phosphate is dephosphorylated by inositol 3-phosphate monophosphatase and transformed into myo-inositol, which is converted in PI with CDP-diacylglycerol in a reaction catalyzed by PI synthase (also called CDP-diacylglycerol-inositol 3-phosphatidyltransferase; Nuwayhid et al, 2006). In the E. histolytica genome, there is one CDP-diacylglycerol-inositol 3phosphatidyltransferase (EHI_069630), an enzyme related to the synthesis of CDP-diacylglycerol, suggesting that PI synthesis pathway is conserved in this parasite.…”
Section: Pi and Phosphoinositides Synthesis And Metabolismmentioning
confidence: 99%